Regulatory restrictions on US bank funding sources: A review of the treatment of brokered deosits - James R. Barth; Wenling Lu; Yanfei Sun (Journal of Risk and Financial Management, 2020)
This paper is the first paper to provide a comprehensive review of the US regulatory treatment of a relatively recent and controversial source of funds, namely brokered deposits. To do this, we consider the extent to which banks rely on brokered deposits, as well as the impact of these funds on bank performance, bank failures, and bank failure costs. We also consider the changes taking place in technologies and how they continue to affect the way banks obtain funds and provide services to their customers. Our conclusion is that, without sufficient evidence to the contrary, such deposits should be treated no differently from all other deposits and other purchased funds.
Keywords: 330; US bank regulation; bank performance; bank funding sources; brokered deposits